Fps1p channel is the mediator of the major part of glycerol passive diffusion in Saccharomyces cerevisiae : artefacts and re-definitions - Oliveira, Rui Pedro Soares de (2003)
Comunicação apresentada no "XXIth International Conference on Yeast Genetics and Molecular Biology", realizado em Gotemburgo, Suécia, em 2003.